(3GdSQ GdSJGQ hSQ GdCSQGQs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI agPG cJGH JQLeJg cJH GdMceGA ajeG QeRhg ef cdGege GdMb heGPcQh hUaj eUGMage aj GNJdGa JOGHjQge aTQMJg dc dJgOj Hg s
(3BNQgG (B:s
(3hde GcJe hde GLO aGSdc HYXeI Gddg dGdG eG MaXJg hVefJg s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
mlirg
Keywords: (3GdcjejGA h GdWHjYjGJs